THE THE READABILITY OF JUNIOR’S LEVEL IN MENTARI’S TEXTBOOKS : A SYSTEMIC FUNCTIONAL LINGUISTIC STUDY - Neneng Farida Rahmah (Ma'soem University, 2022)
This study deals with Lexical Density (LD) and Grammatical Intricacy (GI) of juniors’ level in Mentari’s textbook to measure the readability of the text in the level. The objectives of the study are to find out the GI and LD which performed in the reading text of Mentari’s textbook and the highest readability in the level of the textbook. The main theory used in this study is the theory of Halliday (1985). This study was conducted by descriptive method with qualitative approach. The data analysis of this study was reading text of Mentari’s textbook for junior’s level. The result of the research revealed: (1) the average score of GI in each level are 1.42 in CONNECT1, 1.42 from CONNECT2, 1.42 in CONNECT3 and 1.41 in the CONNECT4. While, the average score lexical density in each level was CONNECT1 as 59.39 %, CONNECT2 as 63.18%, CONNECT3 as 58.60 % and CONNECT4 as 59.00%. (2) CONNECT2 is the highest lexical density of the textbooks, the result also showed that CONNECT 2 as the hardest text of the level in the juniors’ level.